Empowering an Indonesian Diaspora Micro Enterprise Abroad: A Multi University International Community Service on Financial Management, Digital Marketing, and Cross Cultural Communication at Warung Jaya Mba Tia, Busan, South Korea - Asri Dewi; Rabiatul Adwiyah; Hendrati Dwi Mulyaningsih; Azzahra Nurul Hidayah; Hamidah Nawal Rasyadah; Vania Sherryl Liem; Raisah Adila Meliala; Ari Wirokka (International Journal Of Community Service, 2026)
Diaspora owned micro, small, and medium enterprises (MSMEs) play a distinctive role in sustaining cultural identity and economic self reliance among migrant communities, yet they frequently operate with limited financial literacy, minimal digital marketing capacity, and constrained cross cultural service skills. This article reports an international community service activity conducted on 9 July 2026 at Warung Jaya Mba Tia, an Indonesian diaspora culinary micro enterprise located near Gukje Market and BIFF Square in Busan, Republic of Korea, as part of the Mobility Program Day of INOBIST – the 3rd International Conference of Business Administration and Communication (ICoBAC). The activity was jointly organized by the Management Study Program of the Faculty of Economics and Business, Universitas Islam Bandung (UNISBA), together with delegations from Tongmyong University, Universitas Sangga Buana YPKP Bandung, Universitas Bina Darma Palembang, and Universitas Cendrawasih. Using a participatory lecture discussion method, the lecturer team delivered three modules: (1) basic financial management and bookkeeping for micro enterprises, (2) digital marketing strategy for diaspora culinary businesses, and (3) cross cultural communication in customer service. Results indicate that the activity strengthened the business owner's understanding of separating personal and business finances, simple daily transaction recording, and cost based pricing, while introducing practical digital visibility tools such as social media branding and digital map platforms. Findings are discussed in relation to the financial literacy, migrant entrepreneurship, digital marketing, and cross cultural service literature. The activity also created reciprocal benefits for the student delegation and reinforced interuniversity collaboration in international community service, illustrating a concrete model of higher education's Tri Dharma contribution to diaspora communities abroad.